The Role of Capital Expenditure Allocation in Mediating Regional Financial Performance on Regional Economic Growth Aceh Province - Fajrialshah Amarul Haq; Lela Nurlaela Wati; Meita Istianda (Research Synergy Foundation, 2023)
This study aims to examine the role of capital expenditure in mediating the relationship between regional financial performance and economic growth in Aceh Province. The data source for this research uses secondary data sources from the Ministry of Finance and the Central Bureau of Statistics. Respondents in this study were local governments in Aceh with a total of 24 provincial, district, and city governments for 12 years from 2011-2022 period. The results of the analysis show that regional financial performance, as represented by the independence ratio, effectiveness ratio, efficiency ratio, harmony ratio, and personnel expenditure ratio, simultaneously has a positive and significant effect on capital expenditure. Meanwhile, the direct effect of capital expenditure allocation and regional financial performance is represented by the independence ratio, effectiveness ratio, efficiency ratio, harmony ratio, and personnel expenditure ratio, which simultaneously have a positive and significant effect on economic growth. This study found that the mediation of capital expenditure allocation on regional financial performance in Aceh province does not affect economic growth. Capital expenditure which is expected to be able to bridge regional financial performance indicators on economic growth, has not yet affected Aceh province.